Review on Enhanced Interior Gateway Routing Protocol (Global Journal of Computer Science and Technology, 2013)
Routing means to select path in a network and forward a packet through the network to another device on different network. Routing protocols play a vital role in computer network infrastructures. In this research comparison of various routing protocols is made. It been seen that OSPF and EIGRP are the protocols mostly used nowadays. On comparison, EIGRP is considered as the best routing protocol because it maintains the backup routes and also due to its simple configuration and also it supports the unequal cost load balancing which is not supported by other routing protocols.
Keywords: EIGRP; DUAL; OSPF; RIP; hybrid